2011
DOI: 10.1364/ol.36.003861
|View full text |Cite
|
Sign up to set email alerts
|

Negative group velocity and three-wave mixing in dielectric crystals

Abstract: We investigate extraordinary features of optical parametric amplification of Stokes electromagnetic waves that originate from the three-wave mixing of a backward phonon wave with negative group velocity and two ordinary electromagnetic waves. Such properties were earlier shown to exist only in plasmonic negative-index metamaterials that are very challenging to fabricate. Nonlinear optical photonic devices with properties similar to those predicted for negative-index metamaterials are proposed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Similar resonance occurs in the free electron laser in which the low frequency plasma and laser waves are excited by the sum frequency undulator wave in the electron rest frame [19]. It also appears when electromagnetic waves interact with optical phonons in dielectric crystals [20][21][22]. In the literature, another type of combination resonance, namely the difference combination resonance, has been discussed in mechanical systems since the 1960's (see, e.g., [23][24][25][26]).…”
Section: Introductionmentioning
confidence: 85%
“…Similar resonance occurs in the free electron laser in which the low frequency plasma and laser waves are excited by the sum frequency undulator wave in the electron rest frame [19]. It also appears when electromagnetic waves interact with optical phonons in dielectric crystals [20][21][22]. In the literature, another type of combination resonance, namely the difference combination resonance, has been discussed in mechanical systems since the 1960's (see, e.g., [23][24][25][26]).…”
Section: Introductionmentioning
confidence: 85%
“…Such atypical extraordinary behavior in readily available crystals may find exciting applications. However, the estimates have shown that intensity of the fundamental field which is to attain such extraordinary amplification appears close to the optical breakdown threshold [33]. It is because of fast phonon damping and corresponding high rate of energy conversion of the fundamental beam in heat.…”
Section: Mimicking Nonlinear Optics Of Backward-waves In Fully Dielecmentioning
confidence: 99%
“…Thus the proposed approach allows to mimic the unparallel properties of coherent NLO energy exchange between the ordinary and BW. In [33], SRS on optical phonon was investigated in continuous wave regime. The possibility of distributed-feedback type resonance enhancement of amplification has been shown that stem from negative dispersion of elastic waves.…”
Section: Mimicking Nonlinear Optics Of Backward-waves In Fully Dielecmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, this problem was analyzed in [3,[17][18][19]. When the first artificial media, metamaterials, came into existence (a review of properties of metamaterials can be found in [20,21]), investigation of linear and nonlinear properties of backward waves was further stimulated [22][23][24][25][26][27][28]. The reason for this is that it became possible to fabricate a metamaterial exhibiting negative refraction in a certain frequency range, thus supporting the propagation of backward waves [3,19].…”
Section: Introductionmentioning
confidence: 99%